2018
DOI: 10.1177/0093650218803537
|View full text |Cite
|
Sign up to set email alerts
|

Attending to the Mobile Text Summons: Managing Multiple Communicative Activities Across Physically Copresent and Technologically Mediated Interpersonal Interactions

Abstract: This article presents a qualitative investigation of communication practices interactants use to manage mobile phone activity while they are engaged in a copresent conversation. Drawing from conversation analysis and a collection of naturalistic video recordings, our study of mobile phone use in situ focuses on how participants orient to the mobile text summons, the audible chimes or vibrations that indicate the receipt of a text message (or short message service [SMS]). In these moments, interactants must sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…For example, there are minimal forms of sharing activities where the smartphone itself remains in the hands of one interaction partner, but the content retrieved is incorporated into the conversation. This can occur when reading text messages aloud, when providing visual access to the images on the smartphone screen, or when collectively searching the internet for information via one device (Brown et al, 2015;DiDomenico et al, 2018;Raclaw et al, 2016;Weilenmann & Larsson, 2001). Even though the other interaction partners do not hold the device in their hands, they are not excluded from the activity with the smartphone.…”
Section: Integrating Smartphones Into F2f Conversationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there are minimal forms of sharing activities where the smartphone itself remains in the hands of one interaction partner, but the content retrieved is incorporated into the conversation. This can occur when reading text messages aloud, when providing visual access to the images on the smartphone screen, or when collectively searching the internet for information via one device (Brown et al, 2015;DiDomenico et al, 2018;Raclaw et al, 2016;Weilenmann & Larsson, 2001). Even though the other interaction partners do not hold the device in their hands, they are not excluded from the activity with the smartphone.…”
Section: Integrating Smartphones Into F2f Conversationsmentioning
confidence: 99%
“…Different ethnographic studies indicated that smartphones can be integrated into conversations in terms of collective information https://doi.org/10. 5771/2192-4007-2020-4-516, am 16.04.2021, 07:18:48 Open Access --http://www.nomos-elibrary.de/agb Full Paper seeking or sharing activities, such as reading text messages aloud and showing images (e.g., Brown, McGregor, & McMillan, 2015;DiDomenico, Raclaw, & Robles, 2018;Ictech, 2019;Raclaw, Robles, & DiDomenico, 2016;Weilenmann & Larsson, 2001). Even though such sharing activities occur in one-third of all usage moments (Vanden Abeele et al, 2019), they have not yet been studied experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Goodwin 2007), including assessments around technological behavior (e.g. Robles et al 2018). It also illustrates how elicited forms of talk can be examined for what they communicate about society, and also how they communicate that society into being, for the participants.…”
Section: B E M O a N I N G N E W T E C H N O L O G Y A S A F O R M O mentioning
confidence: 99%
“…Over the past decade there has been an increasing focus on NCTs such as smartphones and mobile devices, and social media platforms such as social networking and online dating sites and apps, as a feature of, and embedded in, social interaction (e.g. Ling, 2004, 2008; Arminen 2005; Haddington & Rauniomaa 2011; Laursen 2012; DiDomenico & Boase 2013; DiDomenico, Raclaw & Robles 2018; Brown, McGregor, & McMillan 2014; Rivière, Licoppe, & Morel 2015; Raclaw, Robles, & DiDomenico 2016). This research shows how opinions about technology are not just about individuals, but are social, cultural, political, and linguistic, with users attaching a variety of positions toward NCTs’ expressiveness, utility, and affectivity (Gordon, Al Zidjaly, & Tovares 2017)—not just in the norms they reflect, but also in situated meanings and societal ideologies they construct (Thurlow & Brown 2003; Arminen, Licoppe, & Spagnolli 2016).…”
Section: Attitudes Toward New Communication Technologiesmentioning
confidence: 99%
“…Schegloff (1972) was not specifically concerned with mobility and change in contextual configurations of parties to talk-in-interaction, as communication technology did not allow ‘connected presence’ (Licoppe, 2009) back then. Building on the foundational work he carried out, which scrutinized alternative formulations for describing entities or activities, locational inquiries have been scrutinized in conversational analytic studies in mobile telephony (Arminen, 2006; DiDomenico et al, 2018; Green, 2002; Hutchby and Barnett, 2005; Laurier, 2001; Laursen and Szymanski, 2013; Licoppe, 2009; Weilenmann, 2003). The findings have revealed that unlike landline calls in which co-participants’ respective locations rarely become relevant as talk unrolls, in mobile phone calls, parties frequently inquire about and display mutual understanding of each other’s location.…”
Section: Introductionmentioning
confidence: 99%